American military technology the life story of a technology - Hacker, Barton C.; Vining, Margaret (Greenwood technographies, 2007)
War is part of American history. This book examines how military technology both molded and reflected interactions between the American military and other American institutions. It also aims to provide a springboard for understanding the complex relationship of science, technology, and war in American history